Inverted CsPbI3 perovskite solar cells with all solution processed layers fabricated in high humidity - Sangwon Lee; Sujin Cho; Seok-Hyun Jeong; Wonkyu Lee; Dowon Pyun; Jiyeon Nam; Ji-Seong Hwang; Youngmin Kim; Jihyun Jang; Yoonmook Kang; Donghwan Kim; Hae-Seok Lee (Communications Materials)
Abstract CsPbI3, an inorganic perovskite with an excellent bandgap and thermal stability, exhibits great potential for Si-perovskite tandem solar cells although it is highly sensitive to moisture. Here we address this by fabricating CsPbI3 solar cells under high humidity, controlling annealing via the humidity-dependent volatilization of dimethylammonium iodide. Surface passivation with 1,8-diaminooctane (DAO) reduces Pb surface defects, which enhances charge transport and forms a hydrophobic, moisture-resistant film. The DAO-passivated CsPbI3 solar cell achieves a power conversion efficiency of 17.7% and retains 92.3% of its initial efficiency after 1500 minutes of maximum power point tracking in 30% relative humidity without encapsulation, demonstrating improved humidity stability. All solution-processed layers were fabricated in ambient air, highlighting their potential for cost-effective mass production.